Repercussions on the liquidity of micro-companies located in the district of La Victoria, city of Lima, originated by perceptions of the General Sales Tax on imports to vehicle spare parts - Chiscul Padilla, Miguel Angel (2021)
This article tries to see the repercussions on the liquidity of micro-companies located in the district of La Victoria, city of Lima, generated by the payment of the Perception of the General Sales Tax that is levied on imports of vehicle parts. The General Sales Tax (IGV) is a tax levied on the transfer of goods and services carried out in our country, including construction contracts, first sale of real estate and imports. Demonstrate its negative impact that affects the fulfillment of its short-term commitments. All importers must advance the payment of the General Sales Tax in favor of the Treasury, to later deduct it when it corresponds to pay said tax, that is, when said imported goods are sold, that is, in other words that the referred payment constitutes financing that is it does in favor of the state at the expense of the liquidity of the importers. Sometimes entrepreneurs resort to bank loans to be able to comply with this obligation in order to nationalize imported goods, generating cost overruns for the interest they generate and negatively affecting the profitability of the company.